2019
DOI: 10.1111/cea.13445
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0005519 increases IL‐13/IL‐6 by regulating hsa‐let‐7a‐5p in CD4+ T cells to affect asthma

Abstract: Background: Circular RNAs (circRNAs) are a class of non-coding RNAs that could serve as novel biomarkers for the diagnosis and treatment of diseases. We hypothesized that circRNAs of CD4 + T cells are involved in asthma. Objective:In this study, we investigated the circRNA expression profile and the possible mechanism by which hsa_circ_0005519 participates in asthma. Methods:The expression profiles of circRNAs in CD4 + T cells were revealed by circRNA microarray. Hsa_circ_0005519 expression in CD4 + T cells wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 45 publications
0
52
0
Order By: Relevance
“…According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standard, 47 the standard literature selection process was conducted as shown in Figure 1. We finally included 72 articles 21,22,[25][26][27][28][29][30][31] with 4143 patients and 2188 controls based on the inclusion and exclusion criteria. The features of the included research are presented in Table 1.…”
Section: Publication Selection and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standard, 47 the standard literature selection process was conducted as shown in Figure 1. We finally included 72 articles 21,22,[25][26][27][28][29][30][31] with 4143 patients and 2188 controls based on the inclusion and exclusion criteria. The features of the included research are presented in Table 1.…”
Section: Publication Selection and Quality Assessmentmentioning
confidence: 99%
“…Furthermore, the decrease of let-7a-5p in asthma was associated with peripheral blood eosinophil ratio. 22 Compared with non-asthmatics and mild-tomoderate asthmatics, plasma miR-155 level was significantly elevated in patients with severe asthma. 23 Besides, the increased expression of miR-146 was known to inhibit the nuclear factorkappa B factor (NF-κB), this limiting to inflammatory responses in plasma from asthma.…”
Section: Introductionmentioning
confidence: 96%
“…Circ_0005519 expressions between CD4 + T cells and PBMCs were harmonious in asthmatic cases. From the mechanistical perspective, circ_0005519 might bind to hsa-let-7a-5p and mitigate inhabitation for IL-13/IL-6 in CD4 + T cells [50].…”
Section: Circular Rnas In Immune Responses and Diseasesmentioning
confidence: 99%
“…CircRNAs regulate the T cell-mediated immune response, which is critical for tumor immunity. Correlation assays revealed that hsa_circ_0005519 activated the A circRNAs sponge miRNA to release mRNA and regulate transcription indirectly; B circRNAs with RNA-binding protein-binding motifs sponge or decoy RNA binding proteins (RBPs) to regulate transcription; C circRNAs serve as a scaffold for proteins; D circRNAs with internal ribosome entry sites (IRESs) can be translated into peptides or proteins, driven by m6A; E circRNAs regulate transcription of parental genes immune response, as it might induce cytokine IL-13 and IL-6 expression by regulating hsa-let-7a-5p in CD4+ T cells [43]. CircRNA hsa_circ_0012919 contributed to DNA methylation of CD70, a member of the TNF family, by sponging DNA methylation-related miRNAs in CD4+ T cells [44].…”
Section: Circrna and T Cellsmentioning
confidence: 99%